336 PERILAKU HARIAN MONYET EKOR PANJANG (Macaca fascicularis) PADA OBJEK WISATA: STUDY KASUS DI TAMAN WISATA HUTAN KERA BANDAR LAMPUNG, PROVISI LAMPUNG - Albert Zeksen; Sugeng P. Harianto; Yulia Rahma Fitriana; Gunardi Djoko Winarno (Jurnal Hutan Tropis, 2021)
A monkey forest tourism park is a tourist attraction whose function is to preserve the long tailed monkey’s (Macaca fascicularis) population and to benefit it as a tourist attraction. The research was taking place at the Monkey Forest Tourism Park/Taman Wisata Hutan Kera (TWHK) Bandar Lampung in Bandar Lampung City, Lampung Province, in November 2018. This study objective was to understand he interaction between monkeys and tourists influence the daily activities of long-tailed monkeys, by etermining the behavior of eating, resting, and moving. The dialy tourist presence was observed in order to analyse this impact to anaimal behavior. Observations in this research were carried out using the scan sampling method by observing and recording continuously the daily behavior over a certain period of time. The research was conducted in the period of time at 6:00 AM to 18:00 PM WIB with intervals observation time for 30 minutes for 14 consecutive days. The results showed 50% switching behavior, 31% resting, and 19% eating of all daily behavior. Factors that influence the most dominant behavior are the presence of natural food in TWHKis very small and the dependence of long-tailed monkeys to receive food from tourists. A long-tailed monkey’s natural food source at TWHK is the main factor influencing behavior change.The research implication is the enrichment of feed sources both type and amount of feed is important in TWHK